Perspective of Micro Business Financial Behavior (Case-Study On Tape Mom Ashka’s) - Nugrayanti, Rezhy; Hasnidar, Hasnidar; Yusdiman, Yusdiman (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
Financial behavior is the ability or actions carried out by a person in organizing and managing finances, starting with planning, spending, bookkeeping, monitoring, and accountability for the financial resources they have. This research is conducted at the Mom Ashka Sticky Tape micro business which is located in the Tallo subdistrict of Makassar city. The aim of this research is to explore the perspective of microbusiness actors regarding financial behavior. This research used a qualitative case-study approach. The type of data used in the research is primary data, the data collection methods are observation, interviews, and documentation. The results of this research showed that there are several perspectives regarding the financial behavior of Mom Ashka Sticky Tape Micro Business actors, which contradict several theories, namely costs, budgets, and business savings. This showed that Mom Ashka's Sticky Tape Micro business is still not perfect in implementing financial behavior into business. Financial behavior is very influential in running a business, as it can improve and develop a business actor in running a business, starting from the aspect of knowledge regarding how to manage a business, improving marketing and the quality of human resources, up to preparing financial reports. This is one way to the develop of a business therefore, financial behavior is very important to apply to MSME actors.